“Useless degrees”, quality assurance, and employable graduates: neoliberal effects on University Education in Kenya - Ntarangwi, Mwenda (Etnográfica, 2025)
At a time when it is critical to understand humanity and its various forms of socioeconomic and political life, anthropology and other social sciences are being threatened by a neoliberal emphasis on “relevant” courses in universities in Kenya. Universities are suffering from a push for “relevance” at the detriment of their traditional role of being a public good. Using personal experiences, comparative secondary data overview and analysis, I discuss the challenges facing university education in Kenya under neoliberalism. I argue that the erstwhile role of universities serving the public good has been transformed so much that they struggle to be “sustainable” through “income generating activities” and teach “marketable courses” that will guarantee graduates employment upon graduation. This neoliberal approach to university education follows the growth of a capitalist ethic which started with Structural Adjustment Programs (SAP) that has continually erased the welfare state and turned university education into a commodity and students as customers with preferences rather than as citizens with a right to education. Such a focus is detrimental to cultivating graduates who are well rounded and can respond to the challenges and opportunities of our ever-changing world.